Globalization and occupational health: a perspective from southern Africa - Loewenson Rene (The World Health Organization, 2001)
Increased world trade has generally benefited industrialized or strong economies and marginalized those that are weak. This paper examines the impact of globalization on employment trends and occupational health, drawing on examples from southern Africa. While the share of world trade to the world's poorest countries has decreased, workers in these countries increasingly find themselves in insecure, poor-quality jobs, sometimes involving technologies which are obsolete or banned in industrialized countries. The occupational illness which results is generally less visible and not adequately recognized as a problem in low-income countries. Those outside the workplace can also be affected through, for example, work-related environmental pollution and poor living conditions. In order to reduce the adverse effects of global trade reforms on occupational health, stronger social protection measures must be built into production and trade activities, including improved recognition, prevention, and management of work-related ill-health. Furthermore, the success of production and trade systems should be judged on how well they satisfy both economic growth and population health.